Tanggung Jawab Asuransi Astra Terhadap Tertanggung Atas Kehilangan Sepeda Motor Yang Masih Dalam Proses Kredit - Purwasaputri, Bella Adinda; Yasa, I Wayan; Kusuma, Ajeng Pramesthy Hardiani (PT Matra Cendikia Abadi, 2024)
The Insured receives goods in the form of a motorbike on credit and then installments are made to complete the payment in full in accordance with the policy agreement between the Astra Insurance Company and the Insured. The Insurer's guarantee for loss or damage to motor vehicles provided to the Insured in the policy is coverage for collision, impact, overturning, falling over, wrongdoing, malicious acts, theft preceded or followed by acts of violence, fire, wheel damage due to accidents, and reasonable costs incurred for maintenance or transportation to a repair shop. The responsibility provided by Astra Insurance is based on the Standard Indonesian Motor Vehicle Insurance Policy based on partial loss or total loss. The insurance claim given is in cash, according to the market price of the motorbike at the time of the incident minus the amount of outstanding installment debt. The method used in this research is normative juridical legal research. The focus of legal research is by examining the application of rules or norms in applicable positive law. The author uses a statutory regulatory approach and a conceptual approach. The result of study is the liability given based on partial loss is calculated based on the cost of repairs required or replacement of damaged vehicle parts, and the total loss given is calculated based on the actual price, namely the market price of the motor vehicle at the time of the loss. Insurance claims given by Astra Insurance are in the form of cash, not in the form of vehicle units according to the initial installment contract. Astra Insurance will replace a number of losses with money based on the market price of the motorbike at the time of the incident minus the amount of installment debt still owed. Keywords : Astra Insurance ; Credit; Insurance Rerponsibility.